Microsoft Office Word 2003 Introductory and Techniques - Shelly, Gary B. (Course Technology, 2006)
For the past three decades, the Shelly Cashman SeriesÂđ has effectively introduced computers to millions of students, consistently providing the highest quality, most up-to-date, and innovative materials in computer education. We are proud of the fact that our series of Microsoft Office 4.3, Microsoft Office 95, Microsoft Office 97, Microsoft Office 2000, and Microsoft Office XP textbooks have been the most widely used books in computer education. With each new edition of our Office books, we have made significant improvements based on software changes and comments made by both instructors and students. Our Microsoft Office 2003 books continue with the innovation, quality, and reliability that you have come to expect from the Shelly Cashman Series